Analisis Peran Guru bk dalam Mengatasi Masalah Interpersonal Siswa di Lingkungan Sekolah SMP Negeri 2 Seputih Mataram - Alvyatu Zaahra (Jurnal Konseling dan Psikologi Indonesia, 2026)
The purpose of this study is to describe and analyze the role of guidance and counseling teachers in overcoming students' interpersonal problems in junior high school environments and to identify the types of services and support activities used by guidance and counseling teachers to prevent and resolve these problems. This study employed a qualitative descriptive method using a case field research. Data collection techniques included observation, interviews, and documentation with two guidance and counseling teachers at SMP Negeri 2 Seputih Mataram. Meanwhile, the data analysis technique used the Miles and Huberman data analysis model. After data analysis, the results showed that guidance and counseling teachers play a very important role in addressing students' interpersonal problems through various support services and activities, including information services, group guidance, home visits, mediation, and consultation services, which have been implemented well at SMP Negeri 2 Seputih Mataram.